2009
DOI: 10.1007/s11368-009-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and genotoxicity of sediment-associated pentachlorophenol and pyrene influenced by crop residue ash

Abstract: Purpose The bioavailability and potential toxicity of sedimentassociated organic compounds are affected by sorption processes. The particulate matter (ash) from field burning of crop residues is one of the primary sources for environmental black carbon, which is regarded as supersorbent for organic contaminants and may reduce their ecotoxicity. This study aimed to investigate the influence of ash on sedimentassociated organic pollutants' potential toxicity. Materials and methods Pentachlorophenol (PCP) and pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…It has been reported that surface area, porosity and functional groups of BC play important roles in the sorption of organic pollutants (Cui et al 2009;Lou et al 2011). The characteristics of BCs, such as surface area and porosity, helped in capturing pymetrozine through surface coverage, multi-layer adsorption and condensation in capillary pores.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that surface area, porosity and functional groups of BC play important roles in the sorption of organic pollutants (Cui et al 2009;Lou et al 2011). The characteristics of BCs, such as surface area and porosity, helped in capturing pymetrozine through surface coverage, multi-layer adsorption and condensation in capillary pores.…”
Section: Discussionmentioning
confidence: 99%
“…Sorption of organic pollutants to the char was determined by evaluating the genotoxicity to the earthworm Eisenia fetida. The charred rice crop residue, containing some black carbon, at low mixture rates (1%, 3% and 5%) reduced genotoxic damage of the organic pollutants, however at a mixture rate of 10% the rice-char itself caused genotoxic damage to the earthworm [47].…”
Section: Slash-and-burnmentioning
confidence: 99%
“…The neutralizing of soil pH was provided as a reason why earthworms were not deterred from burrowing into the charcoal-soil mixtures [46]. The prospect of using char from slash-and-burn management practices in rice crops in China for reducing environmental contaminants was evaluated [47]. Rice crop residue was charred in the laboratory to mimic field slashand-burn residue and mixed into sediment of 4.7% C and a pH of 6.9.…”
Section: Slash-and-burnmentioning
confidence: 99%
See 2 more Smart Citations